La créativité en question dans les jeux de rôles en entreprise - Emmanuelle Savignac (Communication)
This article explores the relationship between role play and simulation by examining how they are used in the organization of work in the field of management. The author identifies three modalities of creativity in role play: framework building for experimental purposes, flexibility in the manager’s professional practice, and the omnipresence of narration and fiction. The study is based on nearly three years of observation of management games, including situational role play during training, role reversal games, and business theatre.